Agtech implementation for the management of the agricultural sector, in the management of crop production, in the province of Tequendama, Colombia - Osuna Zabaleta, Jesús Maria (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The aforementioned projects constitute technological innovation that provide solutions to problems and challenges that agriculture faces today in Colombia, in the province of Tequendama, where we are generating transformative changes in the way crops are produced. Under this proposal, the Systems Engineering academic program is articulated with the Girardot Regional Agenda of the Social Innovation Science Park (PCIS) of the Minuto de Dios University Corporation - UNIMINUTO, with the Tena-Tocaima corridor establishing a study area under the approach Participatory Action Research – IAP. Where areas and sectors of innovation such as: new production systems, genetics and protection of crops and animals, Big Data & Precision agriculture, Management, software and information and education services for agricultural producers and Innovative platforms for buying and selling, services outsourcing and financing are beginning to intervene through academic programs, business and the external sector.